RETREG1/FAM134B mediated autophagosomal degradation of AMFR/GP78 and OPA1 —a dual organellar turnover mechanism. Issue 7 (3rd July 2021) - Mookherjee, Debdatto; Das, Subhrangshu; Mukherjee, Rukmini; Bera, Manindra; Jana, Swadhin Chandra; Chakrabarti, Saikat; Chakrabarti, Oishee
ABSTRACT: Turnover of cellular organelles, including endoplasmic reticulum (ER) and mitochondria, is orchestrated by an efficient cellular surveillance system. We have identified a mechanism for dual regulation of ER and mitochondria under stress. It is known that AMFR, an ER E3 ligase and ER- a ssociated d egradation (ERAD) regulator, degrades outer mitochondrial membrane (OMM) proteins, MFNs (mitofusins), via the proteasome and triggers mitophagy. We show that destabilized mitochondria are almost devoid of the OMM and generate "mitoplasts". This brings the inner mitochondrial membrane (IMM) in the proximity of the ER. When AMFR levels are high and the mitochondria are stressed, the reticulophagy regulatory protein RETREG1 participates in the formation of the mitophagophore by interacting with OPA1. Interestingly, OPA1 and other IMM proteins exhibit similar RETREG1-dependent autophagosomal degradation as AMFR, unlike most of the OMM proteins. The "mitoplasts" generated are degraded by reticulo-mito-phagy – simultaneously affecting dual organelle turnover. Abbreviations: AMFR/GP78: autocrine motility factor receptor; BAPTA: 1, 2-bis(o-aminophenoxy)ethane-N, N, N′, N′-tetraacetic acid; BFP: blue fluorescent protein; CCCP: carbonyl cyanide m-chlorophenyl hydrazone; CNBr: cyanogen bromide; ER: endoplasmic reticulum; ERAD: endoplasmic-reticulum-associated protein degradation; FL: fluorescence, GFP: green fluorescent protein; HA: hemagglutinin; HEPES: 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid; IMM: inner mitochondrial membrane; LIR: LC3-interacting region; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MFN: mitofusin, MGRN1: mahogunin ring finger 1; NA: numerical aperature; OMM: outer mitochondrial membrane; OPA1: OPA1 mitochondrial dynamin like GTPase; PRNP/PrP: prion protein; RER: rough endoplasmic reticulum; RETREG1/FAM134B: reticulophagy regulator 1; RFP: red fluorescent protein; RING: really interesting new gene; ROI: region of interest; RTN: reticulon; SEM: standard error of the mean; SER: smooth endoplasmic reticulum; SIM: structured illumination microscopy; SQSTM1/p62: sequestosome 1; STED: stimulated emission depletion; STOML2: stomatin like 2; TOMM20: translocase of outer mitochondrial membrane 20; UPR: unfolded protein response.